Paediatric end-stage renal disease and renal replacement therapy in Switzerland: survival and treatment trends over four decades (Swiss Medical Weekly, 2020)
BACKGROUND Renal replacement therapy for paediatric end-stage renal disease (ESRD) has developed steadily since its introduction five decades ago. Continuous and long-term analysis of patient outcomes is essential for quality control. METHODS The Swiss Paediatric Renal Registry, founded in 1970, includes patients diagnosed with ESRD, defined as dialysis for more than three months or renal transplantation, at age